Influence of personality and destination image on the choice of a tourist destination (purchase intention) - Calle, Marcelo (2024)
The tourism sector has been most affected by the COVID-19 coronavirus pandemic, generating decreased mobility to tourist destinations, economic losses, and job uncertainty. As a result of these events, the importance of contributing with research that helps the economic reactivation of this sector is justified since understanding consumer behavior (tourists) could pose a challenge for marketing specialists and managers of tourist destinations. This study attempts to determine if personality and destination image influence young people when choosing their tourist destination and provide the information that managers of tourism organizations lack due to the limited research on these variables. Through the literary review, it was identified that the image and personality of the destination could influence the tourist’s decision to choose a tourist  destination. The methodology was carried out under descriptive research, with a quantitative approach, by applying surveys using validated questionnaires. The results determine the positive influence of the  abovementioned variables in choosing a tourist destination. The conclusions can help administrators of different tourist destinations develop strategies according to what consumers possibly value most when deciding their next destination to visit, and this can stimulate the economy of a particular place.